Characterization of New Bone Morphogenetic Protein (Bmp)-2 Regulatory Alleles - Shah, Tapan A. (Genesis, 2017)
Bone morphogenetic protein 2 (BMP2, HGNC:1069, GeneID: 650) is a classical morphogen; a molecule that acts at a distance and whose concentration influences cell proliferation, differentiation, and apoptosis. Key events requiring precise Bmp2 regulation include heart specification and morphogenesis and neural development. In mesenchymal cells, the concentration of BMP2 influences myogenesis, adipogenesis, chondrogenesis, and osteogenesis. Because the amount, timing, and location of BMP2 synthesis influence pattern formation and organogenesis, the mechanisms that regulate Bmp2 are crucial. A sequence within the 3′UTR of the Bmp2 mRNA termed the “ultra-conserved sequence” (UCS) has been largely unchanged since fishes and mammals diverged. Cre-lox mediated deletion of the UCS in a reporter transgene revealed that the UCS may repress Bmp2 in proepicardium, epicardium and epicardium-derived cells (EPDC) and in tissues with known epicardial contributions (coronary vessels and valves). The UCS also repressed the transgene in the aorta, outlet septum, posterior cardiac plexus, cardiac and extra-cardiac nerves and neural ganglia. We used homologous recombination and conditional deletion to generate three new alleles in which the Bmp2 3′UTR was altered as follows: a UCS flanked by loxP sites with or without a neomycin resistance targeting vector, or a deleted UCS. Deletion of the UCS was associated with elevated Bmp2 mRNA and BMP signaling levels, reduced fitness, and embryonic malformations.